Actinobaculum schaalii: An Emerging Uropathogen? - Peyman Tavassoli; Ryan Paterson; Jennifer Grant (Case Reports in Urology)
A. schaalii is a rare uropathogen. We report urosepsis with Actinobaculum schaalii detected serendipitously in blood and urine culture in a 79-year-old with urinary tract obstruction. This paper illuminates the flaws in our current system in detecting A. schaalii and raises awareness among clinicians and laboratory teams.